Traditionalism and Modernism in 18th Century Spanish Philosophy of Law - Pérez Perdomo, Rogelio (1968)
The article focuses on the philosophy of law in 18th century Spain and how traditionalist and modernist schools of thought were reflected in and influenced it. The author notes that Spanish legal philosophy experienced a conflict between its markedly medieval origins and the growing modernism that sought to engulf it. In order to understand the importance of Spanish legal philosophy in the 18th century, the author describes how the key figures in Spanish legal philosophy of that period reacted to the European doctrines that emerged during the time, and what their analysis of those doctrines was. Although these legal philosopher ultimately accepted and incorporated a new philosophy that gave rise to modern natural law, they maintained a hostile attitude towards other modernist currents that were consolidating in Europe at the time.